Determinación de los elementos de los estados contables aplicados a los modelos financiero, social y ambiental (2013)
This paper addresses the issue of the accounting statements from an integral perspective, is to say, in addition to the financial statements, considers in the accounting; environmental statements and social statements, understanding that knowledge in accounting comprises, issues still being discussed to enable accounting, profiled in these dimensions. The accounting has to be making integral information to the integral development. In that sense, the paper presents some considerations to keep in mind about the accounting statements (financial accounting statements, environment accounting statements and social accounting statements) and then presents an inventory of definitions of the considered basic elements of financial statements, but viewed from a perspective economic, environmental and social, these elements are the Assets, liabilities, equity (or capital), income, expenses and costs. At the end of each concept, an analysis and propose a comprehensive definition of each concept, so that it applies to the above dimensions and therefore may provide support for the theoretical design of new accounting statements representing other addition to the economic wealth – financial. is the purpose to be more appropriate for the reality of organization